Implementation of Discipline Principles on the Performance of the Village Consultative Body (BPD) in Marinding Village, Luwu Regency - Putri; Lukman; Andi Uceng; Sundari (POLITICO, 2025)
This study aims to analyze the influence of collaborative governance on bridge construction in Marinding Village, Bajo Barat District, Luwu Regency. Infrastructure development in rural areas often faces challenges such as limited funding, inadequate technical support, and a lack of stakeholder collaboration.The research employed a quantitative approach, using data collected through observation, closed-ended Likert-scale questionnaires, and literature review. A sample of 92 respondents was selected using a random sampling technique, and data analysis was conducted using simple linear regression with the aid of SPSS version 25. The findings reveal that the application of collaborative governance principles falls into the "good" category, with an average percentage score of 73.14%, while the bridge construction outcome was rated "very good" at 82%. The regression analysis yielded a coefficient of determination (R²) of 0.356, indicating that 35.6% of the variation in bridge development is explained by the collaborative governance variable, while the remaining 64.4% is influenced by other factors. This result is supported by a t-value of 7.057 and a significance level of 0.000 (< 0.05), confirming a positive and significant relationship between collaborative governance and bridge development. The study highlights the critical role of participatory, transparent, and sustainable collaborative governance in supporting infrastructure development in rural areas.